The role of inflation in financial development–economic growth link in sub-Saharan Africa - Muazu Ibrahim; Olufemi Adewale Aluko; Vo Xuan Vinh (Cogent Economics & Finance, 2022)
The impact of financial development (FD) on economic growth (EG) is well documented. However, studies on how inflation mediates the impact of FD on EG produce inconclusive findings. Meanwhile, the tripartite relationship among FD, inflation and EG is particularly crucial for sub-Saharan African countries given that these countries are largely inflationary on the back of under-developed financial sectors and low EG. The inconclusive evidence presented by the existing studies limits policy making. This study therefore re-examines whether inflation mediates the FD-EG nexus by utilizing a panel data obtained from 36 countries in sub-Saharan Africa. The study uses the sample splitting threshold approach to investigate this relationship. The findings identify inflation thresholds of 7.65% and 6.76% at which the impact of FD on EG changes sign. Specifically, irrespective of the indicator of FD, higher FD significantly increases EG at low inflation rates. However, beyond the estimated thresholds, the impact of FD on EG is insignificant, revealing that higher inflation does not support the growth-enhancing effect of FD. The research recommends that inflation should be kept below the identified thresholds for FD to spur EG.
Keywords: O47; E44; E31; 330; EG; inflation; threshold; financial development